PENGALAMAN GURU SEKOLAH DASAR DALAM MENGGUNAKAN MEDIA PEMBELAJARAN - Aji Permana Nursidiq; Hamdan Husein Batubara (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article investigates elementary school teachers’ experience with learning media. The method used is descriptive qualitative. The type of research used is field research. The research was conducted at the Public Elementary School and Madrasah Ibtidaiyah in Siwuluh. The data collection technique used comprehensive data through online surveys delivered to 17 teachers and in-depth case study interviews interviewed to 5 teachers, which were selected from 17 competent teachers. Data analysis techniques used were reduction, presentation, and conclusion or verification data. The research outcomes indicated that primary school teachers preferred to use traditional learning media rather than digital learning media because of the higher accessibility and portability. In fact, the teachers reported that they did not use new learning media optimally because they rarely attended the training, so they did not have the skill and confidence. Subsequently, the research outcomes also showed that the teachers’ challenges in using learning media were the lack of support from school principals and parents, insufficient digital learning media, limited facilities and school resources, and limited time allocation for teaching. The finding produced elementary school teachers to be improved and more active and creative in developing their teaching skills. In addition, the principals were also expected to pay more attention to the improvement of school facilities, teacher self-development, parental involvement, and others who were involved in implementing school programs.